Smoking, alcohol consumption, diabetes, body mass index, and peptic ulcer risk: A two-sample Mendelian randomization study - Liu, Yi; Xiao, Zhihan; Ye, Kun; Xu, Linlin; Zhang, Yanping (Frontiers in Genetics, 2023)
Background—Observational evidence has shown that smoking, alcohol, type 2 diabetes and body mass index (BMI) are risks factor for peptic ulcer disease (PUD, including gastric ulcer (GU) and duodenal ulcer (DU)). However, the observed associations may be confounding factors. Herein, we use Mendelian randomization (MR) to examine causal associations smoking, alcohol, type 2 diabetes and BMI and risks of PUD. Methods—We employed 8,17,41,325,82, 231 and 616 identified genetic variants as proxies for age of smoking initiation (AgeSmk), smoking cessation (SmkCes, Current/Former), number of cigarettes smoked per day (CigDay), smoking status (SmkIni, Ever/Never), alcohol consumption, type 2 diabetes and BMI to obtain unconfounded effect estimates on GU and DU level among 452264 participants from the Gene ATLAS; The causal relationship was estimated by using inverse-variance weighted (IVW) as the main method. Sensitivity analyses include Cochran's Q test, MR-Egger test, MR pleiotropy residual sum and outlier (MR-PRESSO), MR-robust adjusted profile score (MR-RAPS). Besides, secondary MR analyses were conducted within summary data using genetic risk scores (GRSs) as instrumental variables (IVs). Results—In our two sample MR analyses, genetic predisposition to smoking (SmkInit) and BMI was associated with an increased risk of GU. The beta were 0.0035 (95% CI, 0.0021, 0.0049, p = 1.56E-06) for smoking (SmkInit) and 0.0021 (95% CI, 0.0009, 0.0033, p = 0.0008) for BMI. Genetic predisposition to smoking (SmkInit) as well as higher genetically predicted BMI were associated with an increased risk of DU. The beta of DU were 0.0029 (95% CI, 0.0017, 0.0041, p = 2.43E-06) for smoking (SmkInit) and 0.0018 (95% CI, 0.0007, 0.0029, p = 0.001) for BMI. No other causal association between smoking (AgeSmk, CigDay, SmkCes), alcohol consumption and type 2 diabetes and GU or DU was observed. Consistent results were obtained in sensitivity analyses. Furthermore, GRS approach showed similar results in the several MR methods. Conclusions—These findings do not support a causal role of AgeSmk, CigDay, SmkCes, alcohol consumption and type 2 diabetes in the development of GU and DU. However, it confirms that SmkInit and BMI have a causal part in the development of GU and DU.